S70 Implementing a COPD discharge bundle on a large scale. (14th November 2013) - Sewell, L; Cheung, M; Mitchell-Issitt, C; Barley, K; Chebbout, C; Msimanga, S; Boyce, S; Steiner, MC; Singh, SJ
Abstract : Introduction: There is emerging interest in the delivery of discharge care bundles to manage patients admitted with an an exacerbation of a chronic disease. This approach has been tested on a limited number of patients and the importance of care bundles has been acknowledged by the BTS. However, it is unclear how COPD discharge bundles could be implemented on a larger number of patients without additonal resources. Objective: We wanted to audit the effect of implementing a COPD discharge bundle to all patients discharged with a primary diagnosis of COPD upon smoking cessation and pulmonary rehabilitation (PR) referral rates and to establish the effect upon length of stay (LoS). Methods: We redeployeda Respiratory Early Discharge Service (REDS) in order to deliver the University Hospitals of Leicester COPD discharge bundle. This is comprised of evidence-based interventions including:referral to smoking cessation and PR services, implementation of a self management plan, assessment of inhaler technique, follow up phone calls at 2 working days and 15 days post discharge. The discharge bundle was delivered by the REDS team from April 2012 to March 2013. The total number of patients discharged with a primary diagnosis of COPD (diagnosis code J41–44) from Glenfield Hospital was collected along with referral rates to smoking cessation and PR services. Mean LoS for those patients receiving the care bundle was also recorded. Results: From April 2012 to March 2013 a total of 1742 patients were discharged with a primary diagnosis of COPD. 1160 of these patients received the COPD discharge bundle. Smoking cessation referrals rose from 23.7% in quarter 1 to 48.3% in quarter 4. Pulmonary rehabilitation referals rose from 39.7% in quarter 1 to 55.9% in quarter 4. Mean LoS for patients who received the discharge care bundle was 6.17 days compared to 7.22 days for 2011–2012. The mean LoS for patients who did not receive the care bundle was 7.08 days. Conclusions: A COPD discharge care bundle can be implemented on a large scale with increased referral rates to smoking cessation and PR services. No increase in LoS was noted dispite redeploying an early discharge service.